An adverse social welfare effect of quadruply gainful trade - Oded Stark; Grzegorz Kosiorowski (University of Bonn, Center for Development Research (ZEF), 2020)
Acknowledging that individuals dislike having low relative income renders trade less attractive when seen as a technology that integrates two economies by merging separate social spheres into one. We define a "trembling trade" as a situation in which gains from trade are less than losses in relative income, with the result that global social welfare is reduced. We show that a "trembling trade" can arise even when trade is more gainful in four ways: through trade the absolute income of everyone increases, the income gap in both economies is reduced, as is the income gap between the trading economies. However, trade brings populations, economies, or markets that were not previously connected closer together in social space. As a consequence, separate social spheres merge, and people's social space and their comparators are altered. Assuming that people like high (absolute) income and dislike low relative income, the aggregate increase in unhappiness caused by the trade-induced escalation in relative deprivation can result in a negative overall impact of trade on (utilitarian-measured) social welfare, if the absolute income gains are not large enough to mitigate the relative income losses.
Keywords: D31; D63; F10; F15; R12; 330; Gains from trade; Increase of incomes; Decrease of income gaps; Integration; Change of social space; Low relative income; Quadruply gainful trade; "Trembling trade"; Social welfare